ASSESSMENT OF THE IMPACT OF SEAWATER ON THE SYSTEM ROPA-PELOID KUYALNIK ESTUARY IN ITS SIMULATION - Е. M. Nikipelova (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2015)
The results of physico-chemical studies of brine – peloids Kuyal’nitskogo estuary (peloids, and the solution of peloids, Ropa: sea water 1: 1). It is shown that the basic physical and chemical properties of peloids (mass fraction of moisture, volume weight, tackiness, shear strength, clogging particles more than 250 microns, the volumetric heat capacity, the content of H2S and sorghum) after 2 months of storage meet the requirements that apply to the peloids. Addition of brine to the sea water in the ratio 1: 1 leads to the final mineralization to maintain 180 g / dm3, which favors the presence of bioactivity therein.